Behaviour change techniques to facilitate physical activity in older adults: What and how - Arnautovska, U.; O'Callaghan, F.; Hamilton, Kyra (Cambridge University Press, 2018)
© 2017 Cambridge University Press. Physical inactivity in older adults presents a significant problem within modern societies globally. Using a mixed-method approach, this study explored strategies for the development and delivery of physical activity (PA) interventions by investigating what behaviour change techniques (BCTs) are useful, and how these techniques should be implemented to be feasible for older adults. Sixty-six older adults completed a survey indicating the most useful BCTs, mapping on to motivational, volitional and automatic factors. Of these, 48 older adults participated in an interview exploring strategies for a PA intervention targeted at older adults. The most useful BCT identified in the survey was autonomy support (61.3%), followed by instruction to perform the behaviour (43.5%) and having a credible source of information about PA (42.6%). The key themes discussed in the interviews included providing support in making an informed choice, instruction on how to perform PA, information about health consequences, social support, goal setting, action and coping plans, behavioural demonstration and practice, and monitoring PA. The interviews also revealed key aspects of programme implementation including face-to-face delivery, followed up with additional materials; low cost; age-appropriate PA level; and individualised approach. Interventions assisting older adults in increasing their PA participation across a range of settings should incorporate BCTs targeting multiple processes, while tailoring their delivery to older adults' preferences to ensure their feasibility in supporting regular PA engagement.